The march : a novel - Doctorow, E. L., 1931- (New York : Random House, 2005)
Union General William Tecumseh Sherman's devastating march through Georgia and the Carolinas during the final years of the Civil War has a profound impact on the outcome of the war.
Accelerated Reader AR
Keywords: Sherman's March through the Carolinas -- Fiction; Sherman's March to the Sea -- Fiction; South Carolina -- History -- Civil War, 1861-1865 -- Fiction; Georgia -- History -- Civil War, 1861-1865 -- Fiction; Historical fiction; War stories